Função pulmonar dos trabalhadores da fundição de metais em uma indústria metalúrgica - Moraes, Mônica Vasconcelos de (2011)
Introduction: Metallurgy is the science of the manipulation of metals from their extraction to the formation of material for general use. During the manufacturing process, metal is subjected to casting procedures, such as melting and molding. The casting of metal involves a high occupational risk to employees involved, as they are exposed to metals in the form of powder or small particles and vapors, and high temperatures at the time of casting. The risks to which employees are exposed include inhalation of particles with subsequent loss of lung function, leading to a variety of respiratory diseases. Although the protective equipments influence the risk exposure and the occupational inhalation of particles with subsequent loss of lung function can generate a variety of respiratory diseases. Objective: To evaluate the impact of the inhalation of gases and pollutants and the high temperatures on pulmonary function of workers in the metallurgical industry. Methods: We conducted a cross-sectional study of all employees in a metallurgical industry working directly in the process of metal casting. Individuals were asked for their medical history and lifestyle assessments were made. And routine spirometry and expiratory peak flow levels were measured. Results: The 63 employees were aged from 18 to 59, with a mean age of 33.98 ± 8.25 years and mean years working in current environment was 6.07 ± 6.47 years. 14.28% of employees were current smokers and 3.17% former smokers. Of all employees evaluated, only 7.93% reported previous respiratory symptoms, only With regard to spirometry, the employees had a mean FVC of 95 ± 18% predicted, FEV 1 of 95.06 ± 15.83% predicted, and an average of 0.82 ± 0.09 FEV1/FVC ratio. The expiratory peak flow of the employees was on average 502.06 ± 120.74 L / min. Conclusion: The spirometry and expiratory peak flow values were within normal limits, considering the mean age, period of employment in the metal industry and without previous pulmonary history, smoking status associated with the absence of co-morbidities